INTERVENSI TARI POCO-POCO TERHADAP FUNGSI EKSEKUTIF PENYANDANG DM TIPE 2 DENGAN HENDAYA KOGNITIF RINGAN MELALUI PERBAIKAN FUNGSI DAN PLASTISITAS NEURON - Ria Maria Theresa, - (2015)
Introduction: An increase in the production of reactive oxygen species (ROS) and free radicals in people with type 2 diabetes results in destruction of cells including neuron and leads to impaired executive function. Executive function is important to be maintained so that persons can perform their functions properly. To maintain or improve executive function, an intervention which is easy, practical and non-expensive is required, which can be in a form of dance so that one can live healthy and independent in order to achieve maintainable quality of life. Poco-poco dance is a folk dance that is popular today, easy to do, inexpensive, and in courteous accordance with Indonesian cultural norms is estimated to have a value of aerobics that may improve or maintain executive function. Subjects and Methods: The subjects were citizens of Depok with type 2 diabetes mellitus and mild cognitive impairment. Experimental test interventions with poco-poco dance were designed as randomized controlled trials (RCTs). This study was conducted in December 2013-July 2014. The respondents, a number of 32 people, aged 45-59 years, at least junior high school graduation, had no impairment of physical activity. Screening used HKVND DM T2. All subjects performed laboratory tests HbA1c, LDL, triglycerides, total cholesterol, F2-isoprostane and brain metabolite ratios NAA/Cr with MRS before and after intervention. Results: There were significant differences in psychometric tests TMT B (p=0.016), HbA1c (p=0.020), LDL (p=0.003), triglycerides (p=0.002) and F2-isoprotane (p=0.001) and NAA/Cr ratios in the right prefrontal (p=0.001), left prefrontal (p=0.001), left parietal (p=0.007) and right hippocampus (p=0.003) before and after poco-poco dance intervention. In the control group there were significant differences in HbA1c (p=0.001) and F2-isoprostane (p=0.001) and no significant differences in TMT B (p=0.99) and in NAA/Cr ratios of all lobes. People with type 2 diabetes mellitus who danced poco-poco improved their executive function by 37.5% versus controls. Conclusions: Performing Poco-poco dance twice a week for 12 weeks can improve executive function through brain plasticity in people with type 2 diabetes mellitus and mild cognitive impairment.